Study of the Application of Pepper (Piper nigrum Linn) Cultivation in the Kao Region, North Halmahera Regency (Agrikan Jurnal Agribisnis Perikanan, 2024)
A number of pepper farmers stopped cultivating pepper plants because their plants died. It is suspected that this happened because farmers did not have knowledge of correct pepper cultivation techniques. This research aims to determine the application of pepper cultivation techniques at the farmer level, which was carried out in the Kao Region. Data was collected by interviewing all 9 pepper farmers, using questionnaires and field observations. The data collected includes knowledge of seeding, land preparation, planting spur poles, planting seeds, maintenance including pruning spurs and vines, controlling weeds, pests and diseases, as well as fertilizing and harvesting techniques. Data analysis was carried out descriptively, where the results were displayed in the form of pictures, graphs and tables. The results show that 90% of farmers have carried out the seeding process, 56% of farmers have carried out seed treatment correctly, 89% of farmers have made seeds from cuttings using the correct technique, 77% of farmers have carried out sharp planting before seeding, 69% of farmers have used spacing. That's right, farmers already have the ability to recognize the characteristics of pepper fruit ready to be harvested. The weaknesses in pepper cultivation practices include only 33% of farmers transplanting seeds to the location, the length of the sharpening poles being less than 3m, the lack of a process for pruning protective plants and controlling weeds, Some pepper plants are attacked by pests and diseases, and fertilizers have not been used in their cultivation activities.LoA, Plagiarism
Keywords: Cultivation practices; Pepper crop; Kao Region